Визначення поняття обставин, що виключають злочинність діяння, у кримінальному праві України - Андрусяк, Ганна Миколаївна (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті на основі узагальнення конститутивних ознак обставин, що виключають злочинність діяння, це поняття визначено як сукупність умов, за наявності яких усвідомлені вольові діяння, подібні до злочину за об’єктивними ознаками, обумовлені суспільно-позитивними (нейтральними) мотивами і цілями та не заборонені законодавством України, що виключає кримінальну відповідальність. Запропоновано відповідну норму закріпити у статті 36 КК України. Виокремлення спільних ознак та загального поняття обставин, що виключають злочинність діяння, дозволить у кожному конкретному випадку визначати належність тієї чи іншої обставини до цього інституту. За наявності об'єктивних передумов, достатніх правових основ, значної поширеності певних діянь, і відповідності їх ознак тим конститутивним ознакам, які включені у загальне поняття, цей інститут може бути розширений. Circumstances excluding criminality of an offence represent one of the most sophisticated institutions of the General part of Criminal Law of Ukraine. This article summarizes the constitutive features of circumstances excluding criminality. Within these features and on the basis of the analysis of scientific approaches to the problem under discussion the following definition has been suggested: circumstances excluding criminality is a set of conditions under which the conscious volitional acts like a crime under objective evidence are caused by social-positive (neutral) motives and goals and not prohibited by the law of Ukraine, and which according to the law exclude criminal responsibility. Accordingly, the proposal on the normative statutory fixing of the concept in Article 36 of the Criminal Code Ukraine was substantiated as follows: «A person who commits a deliberate willful act like the crime under objective evidence, caused by social-positive (neutral) motives and goals and not prohibited by the legislation of Ukraine is not a subject to criminal liability. The court may recognize as such that exclude criminality of an act and other circumstances, which are not specified in section VIII of the General Part of this Code». Singling out the common characteristics and the concept of circumstances excluding criminality of an act in general, will allow to determine in any particular case the correspondence of this or that circumstance to this institution in every particular case.
Definition of the Notion of Circumstances Excluding Criminality of an Offence in the Criminal Law of Ukraine
Keywords: суспільна небезпечність; протиправність; умова; ознака; обставина, що виключає злочинність діяння; social danger; illegality; condition; characteristics; circumstances excluding criminality of an act